Catalytic hydrogen production and method thereof
By designing O-containing catalysts and structure testing methods, combining barrier barrel testing and XPS analysis, catalytic hydrogen production materials with flexible and variable structures were developed, which solved the problems of unstable catalytic effects and lack of materials in the existing hydrogen energy industry. It has achieved efficient catalytic hydrogen production and oxygen production effects, and promoted the development of hydrogen energy.
Patent Information
- Application Number
- CN202410611812.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-08
- Publication Date
- 2024-12-20
AI Technical Summary
The catalytic hydrogen production or oxygen production effect of the existing hydrogen energy industry is unstable, the materials are lacking or the cost is high, the comprehensive research on hydrogen production system is insufficient, the existing oxygen production and oxygen production system cannot be used effectively, and there is a lack of suitable preparation methods and monitoring methods. This leads to limited development of hydrogen energy.
Using O-catalyst-containing test methods and structural test methods, select specific electrodes and test liquids, add O-type catalysts, use barrier barrels to test the solution performance, combine XPS to analyze the affinity of materials, and design a catalytic system with flexible and variable structures. Hydrogen materials, including nickel oxides, FeNi, etc., are combined with photon catalysts to form a stable and anti-reverse catalytic system.
The stability and adsorption efficiency of catalytic hydrogen production have been achieved, the electron transfer efficiency has been improved, the material structure flexibility has been enhanced, and simple and complete preparation and monitoring methods have been formed, which has promoted the development of the hydrogen energy field.
Smart Images

Figure CN119165032A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new hydrogen energy, and in particular relates to a catalytic hydrogen production method. Background Art
[0002] Hydrogen energy is recognized as a clean energy source. Hydrogen energy is the starting point and direction of the transformation of human energy civilization. The development of new energy sources is imminent in today's world. Since the energy used, such as oil, natural gas, coal, and petroleum gas, are non-renewable resources, the reserves on the earth are limited. Fossil energy has negative problems such as pollution and climate environment, and human survival is inseparable from energy, so new energy sources must be found. Although the development of hydrogen energy and hydrogen mines is slow, there is a momentum of vigorous development. However, the current comprehensive solutions for the hydrogen energy industry are insufficient, or the catalytic effect is poor, the hydrogen or oxygen production effect is unstable, the hydrogen or oxygen production materials are lacking or the cost is high, the systematic comprehensive research on hydrogen production is insufficient, the comprehensive system of hydrogen production and oxygen production is lacking, or the existing oxygen production and oxygen production system cannot be effectively used in combination with the effective application system. The existing related new hydrogen production materials also lack corresponding preparation methods, and the supporting methods are imperfect. The existence of the above problems is a serious bottleneck restricting the development of hydrogen energy. Therefore, the above problems need to be solved urgently. Summary of the invention
[0003] In order to solve one of the above problems, the present invention provides a method for testing the catalytic hydrogen production performance of an O-containing catalyst, wherein a workstation is selected, a carbon rod is used as an electrode, a mercury / mercury oxide electrode is used as a reference electrode, sulfuric acid is used as a test liquid under light conditions, and the initial current is tested by voltage. Under the same conditions, a certain mole of O-type catalyst is added as the initial current; the O-type catalyst contains at least the following molecular structure
[0004] Ⅰ
[0005]
[0006] catalyst.
[0007] The present application also provides a method for testing the structure of a hydrogen production catalyst. First, an O1 catalyst is prepared into a solution, and a BVZ-like substance is prepared into a solution. The viscosity of the O1 solution and the BVZ solution is tested. The performance of the solution is tested using an obstacle barrel. The obstacle barrel includes a barrel sleeve, a cutting ring, and an obstacle channel. The O1 solution and the BVZ solution of the same scale are respectively loaded into the obstacle barrel. The obstacle barrel is configured with a 316j1 cutting ring and a 316j1ru cutting ring. The barrel sleeve is pulled up to a certain height to release the tension. The 316j1 cutting ring and the 316j1ru cutting ring are respectively used to The test is carried out once, and the height L of the liquid passing through the two cut circles or obstacle channels and the mass value m of the liquid entering the obstacle channel are measured with the ruler in the barrel sleeve. The height BVZL of the liquid passing through the two cut circles or obstacle channels and the height O1L of the liquid passing through the two cut circles or obstacle channels of the O1 solution are compared to measure the material structure performance or its flexibility. The external surface of the 316j1 cut circle containing the catalyst O1 material and the 316j1ru cut circle contacting the O1 material are tested by XPS to analyze the affinity between the materials.
[0008] Preferably, in the test, the BVZ solution has a stable structure and is not easily damaged when subjected to external pressure and shearing, which is a reflection of the process or result of the test that the BVZ solution has a flexible structure and is well deformed when subjected to pressure and shearing and enters the cutting circle, which is a reflection of the quality of the test process or result; the BVZ solution has a stable structure and releases the pressure and shearing force after entering the cutting circle, and its deformation speed is slightly slower than that of the O1 solution.
[0009] Preferably, in order to check the affinity between the catalyst O1 material and the cut ring, the cut rings 316j1 and 316j1ru containing the catalyst O1 material are subjected to XPS measurement of the external surface of the cut rings 316j1 in contact with the O1 material to measure the characteristic peak of the P element on the external surface of the cut ring 316j1.
[0010] Preferably, the barrier barrel comprises an outer barrel and an inner barrier barrel, a barrel sleeve is arranged in the inner barrier barrel, a cutting ring is threadedly connected to the bottom of the barrel sleeve, an obstacle channel is arranged in the middle of the barrel sleeve, the channel is arranged in a pair of trapezoidal slopes, the opening slope of the upper trapezoid is greater than the opening slope of the lower trapezoid, the upper part of the cutting ring is threadedly connected to the obstacle channel at the lower end of the middle part of the barrel sleeve, the cutting ring can be replaced by screw connection, an elastic column is arranged on the outside of the inner barrier barrel, the inner barrier barrel can seal the elastic column from the measuring liquid in the inner barrel, the bottom plate of the elastic column is fixed to the bottom of the outer barrel, the upper handle of the barrel sleeve is movably connected to the upper part of the elastic column, and the barrel sleeve can be pulled to a certain height by pulling the handle.
[0011] The material of the present invention has a catalytic effect. Furthermore, the material of the present invention has a catalytic or catalytic hydrogen evolution effect. Furthermore, the photon catalysis has the effect of coordinating polynitrogen cations to improve the electron transfer efficiency. The catalytic oxygen production material of the present invention can be used alone, or it can be used in combination with catalytic oxygen production and organic hydrogen production to produce a comprehensive effect. The hydrogen production material further has stability and adsorption efficiency. The structure of the relevant material reflects that the flexible and synergistic structure can make its material have better catalytic properties. Further, the flexible and synergistic structure cooperates with other substances to make the material structure so as to improve the adaptability and synergy of the material of the present invention. The material composed of the present invention is easy to obtain, and the material structure is beneficial to the composition of a stable catalytic hydrogen production process system. The composition system prevents backflow or has anti-reverse characteristics. The invention provides a simple and complete preparation method and monitoring method, which is of great significance in the fields of catalysis, hydrogen production process, hydrogen production material, and hydrogen production equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0013] Figure 1 : XRD diffraction pattern of material A;
[0014] Figure 2 : XRD detection spectrum of material A1;
[0015] Figure 3 : Electron microscope image of material B;
[0016] Figure 4 : XPS electron energy spectrum of material B;
[0017] Figure 5 : XRD diffraction pattern of C material surface;
[0018] Figure 6 ::Infrared spectrum test chart of O1 catalyst;
[0019] Figure 7 : XRD diffraction pattern of X1 material;
[0020] Figure 8 a: Electron microscope image of X1 material;
[0021] Figure 8 b: Electron microscopy information of X2 material;
[0022] Fig. 9 : XRD diffraction pattern of X2 material;
[0023] Fig.10 : XRD diffraction pattern of BV crystal;
[0024] Fig.11 : XRD diffraction information of BV (k2Al 24O 37) material;
[0025] Fig.12a : Oxygen evolution performance test diagram of the material of the present invention;
[0026] Figure 12b : Hydrogen evolution performance test diagram of the material of the present invention;
[0027] Fig.13 a: Schematic diagram of the static cross section of the obstacle barrel;
[0028] Fig.13 b: Schematic diagram of the cross section of the barrier barrel when the barrel sleeve is pulled up to a certain height;
[0029] Fig.14 : Enlarged schematic diagram of the cut circle in the cross-section diagram of the barrier barrel;
[0030] Fig.15 : XPS test image of the outer surface of the cutting ring in contact with the O1 material. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A new hydrogen energy material, at least composed of different structures or systems of group VIII elements to achieve catalysis, the system includes an anti-reversal system, a catalytic hydrogen or oxygen production system composed of different structural materials, the hydrogen production and oxygen production or their system constitute an anti-reversal system, the catalytic hydrogen or oxygen production system composed of different structural materials, combined with the catalytic principle, the structure includes defect structure, lattice oxygen, material structure, material surface activity, etc., which are beneficial to the potential or electron transfer efficiency. The hydroxyl group in the material of the present invention has a material formation increase structure, and further the hydroxyl group has a repulsive force at a certain fixed position or combines with photoelectricity to increase the current, combines with a small amount of lattice oxygen and lattice oxygen collaborative design to increase electronegative substances, the sliding structure of the present invention is beneficial to the adsorption and absorption effect, or is beneficial to the oxide effect, such as the beneficial nickel oxide positive effect, the catalytic hydrogen production system includes using hydroxyl or hydroxide ion structure materials composed of nickel and oxygen elements to catalyze hydrogen production or using Ni3(BO3)2 or FeNi materials to catalyze hydrogen production or using BaMn8O 16 Catalytic hydrogen production or photon catalyst containing molecular structure I / molecular structure II material catalytic hydrogen production or the material is composed of at least two chemical structure materials of the present invention, the internal hydroxyl material containing MoO·HO or the internal hydroxyl material containing Cu7x (Mo+6)2(Mo+2)O 12 (OH) 4, Internal hydroxyl materials or materials containing MoO·HO or materials containing Cu 7x (Mo+6)2(Mo+2)O 12 The (OH)4 internal hydroxyl material is provided with a trivalent boron acid oxide amorphous material structure to form a catalytic oxygen production system, the hydrogen production material includes BaMn8O16, BaMn8O16 at least partially reacts with a photon catalyst to generate the following structure III substance through a modification reaction, BaMn8O16 is a polyhedron or a variable structural defect structure, the structure III substance is adsorbed on an insulating material silicon dioxide with a slightly larger particle size than BaMn8O16 to form a catalytic material, the material containing MoO·HO internal hydroxyl or hydroxide ion groups or containing Cu 7x (Mo+6)2(Mo+2)O 12 (OH) 4, A material with metal ruthenium is arranged on the surface of the internal hydroxyl material to ensure the activity of the O-type catalyst or to form an anti-reversal system. The internal hydroxyl material containing MoO·HO or the internal hydroxyl material containing Cu 7x (Mo+6)2(Mo+2)O 12 (OH) 4, The cerium borate contained on the surface of the internal hydroxyl material can realize catalytic oxygen evolution to adapt to hydrogen production or hydrogen energy materials to form a hydrogen production system, such as catalytic oxygen evolution in water hydrogen production to promote hydrogen production, such as having the potential for continuous reaction to promote catalysis. When the catalytic oxidation is used in water electrolysis to produce hydrogen, the continuous and efficient catalysis of catalytic oxygen production optimizes the conditions or environment for hydrogen evolution, such as low-pressure or low-energy high-efficiency catalysis increases or stabilizes the current of the system, provides proton hydrogen for hydrogen evolution, and further ensures the reverse progress of the system composed of materials such as nickel in the hydrogen evolution catalysis, increases the efficiency of catalytic hydrogen production, and prevents damage to the system or the occurrence of negative effects.
[0033] The following describes the process involved in the present invention, the preparation method of the catalytic oxygen production material:
[0034] The first step is to heat copper nitrate to form a basic salt and ammonium molybdate in a mass ratio of 3:2, preferably 0.3:0.2, and add them into 30g distilled water. Use low concentration nitric acid, such as 1% concentration nitric acid, to adjust the pH value to 4-8, preferably 5-7.5, add 0.1% sodium percarbonate, and self-pressurize and heat react at no more than 200 degrees for 8 hours. The second step is to dry at 200 degrees to form a composition containing MoO·HO substances or containing Cu 7x (Mo+6 )2 (Mo+2)O 12 Material A (OH)4, after XRD baseline calibration, can be found out. Figure 1It can be seen that diffraction peaks appeared at 2θ=34.591°, 29.326°, 23.682°, and 60.943°, which are basically consistent with the standard characteristic peaks of PDF#00-050-1622 card, indicating the existence of Cu3MoO4(OH)4 crystalline substance. At the same time, diffraction peaks of hexavalent molybdenum oxide at 2θ=20.447°, 21.394°, and 25.428° and diffraction peaks of divalent molybdenum alkaline oxide at 2θ=18.785°, 36.65°, and 49.903° appeared. The peak area intensity of copper ions is greater than that of 1622 card, indicating that copper ions increase. It is comprehensively inferred that the produced A material contains Cu 7x (Mo+6 )2 (Mo+2)O 12 (OH)4 crystals, and then adsorb A or a material containing A onto a treated nano copper sheet containing carbon tubes, preferably a copper sheet of 4*2cm-2, to form a catalytic oxygen-producing material or electrode.
[0035] After the first step, the method further includes adding copper nitrate and ammonium molybdate in a mass ratio of 1:1.5 to react, heating the copper nitrate to form a basic salt, preferably adjusting the pH to 6-8 with 0.03-0.15g of ammonium molybdate, and then continuing to react to form reactive or multivalent molybdenum, and then adding 0.01 to 0.1 sodium borate to react for 2-4 hours to form a material A1 containing a component of boron; XRD detection of A1 confirms that a more electronegative borate is introduced, and the electronegative borate changes or increases the vacancy defect structure of the material. If the detection is not achieved, the reaction process is adjusted again, such as Figure 2 A1 showed amorphous broad peaks of acid oxide containing trivalent boron at 2θ=14.93°, 40.8°, 25.82°, 28.5°, 20.15°, and 17.9°, which suggested that the internal hydroxyl material containing MoO·HO or Cu 7x (Mo+6 )2 (Mo+2)O 12 (OH) 4, The internal hydroxyl material structure may contain at least trivalent boron acid oxide amorphous material, denoted as A1. Due to the introduction of more electronegative borate, the vacancy defect structure of the material changes or increases.
[0036] Further, 0.05-0.2 g of ruthenium trichloride is added to 10-30 g of aqueous solution, the second step A material is added, 0.01-0.2 g of disodium ethylenediaminetetraacetate is added, and then 0.1-0.6 g of hydrazine hydrate is slowly and gradually added, not exceeding 0.4 g. After the addition is completed, the material is taken out and placed in an oven at 170-190 degrees for reaction for 2-8 hours. After the material is taken out to room temperature, it is washed with an alcohol-containing polar solvent to obtain a material B containing ruthenium on the surface of the material A; by high-resolution TEM electron microscopy, such as Figure 3 There is a 2.7nm accumulation shadow on the square grains, which may be Cu7x (Mo+6 )2 (Mo+2)O 12 A unit cell of metallic ruthenium is formed on the surface of the (OH)4 material, similar to the structure Figure 3 It can be seen that the concave shape of the material is beneficial to increase surface adsorption and stable protection of the material, and prevent collision damage. XPS analysis of the material surface shows that Figure 4 , at 280.2ev ruthenium element, and the proportion of ruthenium element is relatively high, trace copper appears, indicating that the process of copper ion and copper change reaction has occurred, but the 2p2 / 3 of copper is not obvious, indicating that the surface is mainly copper element, trace divalent ruthenium element weak double peak appears, and there may be trace unoxidized ruthenium. The appearance of titanium and molybdenum of different valences also confirms the A structure and the formation of metallic ruthenium on the surface of the material. The preferred solution is that before adding the ruthenium-containing substance, substance A reacts with boric acid and molybdenum acid hydrate to form the substance containing boron and molybdenum elements in material B.
[0037] Further, the surface of the A1 material is sprayed with cerium chloride droplets in a nitrogen environment, heated preferably at less than 200 degrees for 48 hours under pressure, taken out and cooled, to form a C material containing cerium oxide on the surface of the A1 material, and the A1 material including the surface sample is subjected to XRD analysis such as Figure 5 The diffraction angles of cerium borate are 49.123°, 20.447°, 44.757°26.596°, 21.394°25.428°.
[0038] The above materials have the effect of catalytic oxidation or oxygen evolution. Furthermore, the metal of ruthenium in material B weakens the adsorption of O-type catalyst in the hydrogen production stage, further preventing catalytic oxidation and catalytic efficiency from being reduced. Further, OH plays a role inside the material to increase the adsorption of material A. The high and low valence states of molybdenum in material A improve the conditions for efficient reaction, which is beneficial to promoting the positive progress of the continuous catalytic guarantee system, further ensuring the positive catalysis of alkaline nickel. Further, the presence of OH- inside material A is beneficial to the proximity of ruthenium ions to the copper surface or the coverage of the surface, which is further beneficial to the oxidation of water or OOH and the release of adsorbed oxygen. Further, the cerium redox of material C weakens copper oxidation, which is beneficial to increasing the electron pathway and promoting the oxidation of the containing group. Further, the possible sliding property of the borate structure is beneficial to the rapidity and flexibility of electron transfer and oxidation, so as to realize catalytic oxygen evolution. The reaction between cerium and copper increases the electron pathway, which is beneficial to promoting continuous catalysis. The catalytic oxygen production material of the present invention can be used alone, or it can be used in combination with catalytic oxygen production and organic hydrogen production to produce a comprehensive effect.
[0039] Catalytic materials for the reduction hydrogen production stage use the following photon catalyst of molecular structure I in the hydrogen production process. In order to further cooperate with polynitrogen cations and improve the electron transfer efficiency, a better effect is achieved because the long-chain multi-angle functional groups can collect electrons over a long distance. Photon catalysts of molecular structure II can also be used. Furthermore, the hydrogen production process also includes using a material containing at least NiO(OH) as a catalytic material for the reduction hydrogen production stage, so that OH- can cooperate with other structural materials outside the material to play a role.
[0040] The method for preparing the photon catalyst having the following molecular structure I is as follows:
[0041]
[0042] The first step: adding chlorostyrene and ammonium acrylate in a mass ratio of 2:1 into water for catalytic reaction to produce halogenated aromatic carboxylate.
[0043] Step 2: Mix the halogenated aromatic carboxylate and 4,4'-bipyridine in a 250mL single-necked flask at a weight ratio of 3:2, add 100mL acetone, heat at 60°C, stir and reflux for 3 hours. After the reaction is completed, cool down, filter the precipitate, wash with acetone, and vacuum dry to obtain a photocatalyst, recorded as O. When the process requires, the dried product is hydrolyzed under concentrated hydrochloric acid to obtain a treated catalyst O to increase performance. The catalyst O-type material has the ability to capture electrons or its structure cooperates with ruthenium materials to adjust the production capacity and prevent reverse energy loss.
[0044] Preferably, in the first step, ammonium acrylate can be treated with acrylic acid, preferably acrylic acid or ammonium acrylate, by heating with ethanol and triethylamine to maintain stable performance, and then the step of adding 1 part by mass of vinyl acetate and 3 parts of vinylphosphonic acid to react is included, and when the reflux is almost over, 5 parts by mass of ethanolamine is added and then a few drops of concentrated sulfuric acid are added, and the reaction is heated and measured. If the temperature rise is not obvious, a few drops of DCC / DMAPH can be added, and after accelerating the reaction for 2 hours, DCM / TBDMSOTF can be added. After the reaction, a trace amount of alkali can be added according to the product situation to selectively eliminate the maintenance, cool, filter and dry to form a photon catalyst having the following molecular structure II, recorded as O1, where O1 is a new catalyst of O.
[0045]
[0046] Infrared spectrum test on O1 Figure 6As shown. The absorption peaks at 3600cm-1 for hydroxyl and 3445cm-1 are attributed to the asymmetric stretching vibration of secondary amine, the absorption peak at 3025cm-1 is attributed to the stretching vibration of unsaturated CH on the benzene ring, 1745cm-1 is a strong absorption of ester group, 1685, 760cm-1 are characteristic peaks of pyridine, 1619cm-1 is attributed to the stretching vibration of carboxyl C=O, 1455cm-1 is attributed to the C=C vibration of benzene ring skeleton, and the absorption peak of phosphoric acid is around 1250cm-1, 913~13 The absorption peak at 04cm-1 is the stretching vibration of the CH bond on the benzene ring, the absorption peaks at 699cm-1 and 424.37cm-1 are the absorption of the benzene ring group, and the absence of a strong peak at 1600cm also confirms that the O-type catalyst component in the first step of the substance is generated by the reaction. O1 has a catalytic effect, and further has the role of a synergist and an electron regulator. The above photon catalysts can be used alone or in combination with other catalytic materials, such as in combination with inorganic catalysts. The photons include the required light and can be used in combination with other catalysts.
[0047] The following describes a method for preparing a material X comprising at least NiO(OH) in a catalytic hydrogen production system, wherein X includes X1 or X2;
[0048] Step 1: Weigh nickel formate and sodium hydroxide in a mass ratio of 15:4, with an excess of alkali. After filtering, add a small amount of preferably 2 g of 10% hydrogen peroxide solution to the precipitate to prevent excessive oxidation of nickel. Heat-treated material X1 containing NiO(OH) is subjected to XRD detection. Figure 7 It can be seen that the diffraction peaks of 2θ appear at 48.005°, 35.804°, 46.434°, 40.746°, 37.039°, and 19.2°, indicating that NiO(OH) crystals are formed. Figure 8 , Figure 8 A bevel of about 15 nm was found in a, and this result is consistent with the xrd Figure 1 The material containing NiO(OH) crystal structure and the treated carbon nanotubes are added into water for reaction and adsorption to form a carbon nano-hydrogen production material or electrode;
[0049] Furthermore, no more than 3 g of hydrazine hydrate is added to the first step filtrate to prevent excessive reaction of hydrazine hydrate for at least 8 hours, and then iron carbonate is added first and then ethylene glycol is added in a mass ratio of 1:1 to prevent excessive ethylene glycol. The reaction process monitoring includes the oxidation of nickel atoms reduced by hydrazine hydrate by trivalent iron ions, and the oxidation of iron ions by oxygen after being reduced. Then borax is added and stirred evenly until the pH reaches 6-8. The mixture is added and placed in an aging kettle for ultrasonic aging at 90-120 degrees for 20 hours, and then dried below 200 degrees to form nickel borate iron or Ni3(BO3)2 or FeNi powder on the basis of NiO(OH), which is recorded as X2. XRD analysis of X2 is performed as follows: Fig. 9The peaks at 2θ of 36.477°, 55.573°, 22.62°, 40.532° and 33.839° are inferred to contain NI3(BO3)2. The peaks at 2θ of 50.962°, 44.652° and 44.63° should be FeNI. Because other characteristic diffraction patterns overlap, it is inferred that it may contain FeNio2BO3. The electron microscope of X2 is as follows: Figure 8 In b, there are oblique lines of about nanometers on the oblique edge surface, which should be FeNi attachments. Figure 8 The squares in b corresponding to the positions greater than 15 nm in a are speculated to exist on the surface of NI3(BO3)2, which can further improve the stability and adsorption efficiency of the material by forming Ni3(BO3)2 or FeNi or FeNi2O2BO3;
[0050] Furthermore, in order to expand the catalytic properties of the hydrogen production material of the present invention including the x material, a substance containing BaMn8O16 is prepared. The specific preparation process is as follows: first, barium chloride, ammonium acetate, and glycerol are dissolved in water in a molar ratio of 1:1:1, and heated to react for 6 hours. Preferably, a clear solution is produced to stop the reaction to form a solution. Secondly, manganese hydroxide and hydrochloric acid are introduced into oxygen in a molar ratio of 1:2 to react to form a colored turbid substance containing multiple OH-, and the manganese content is kept to exceed 35% of the total amount of the synthetic substance. The solution containing 6 moles of barium is first added by mole, and added to the liquid surface through a liquid adding device to ensure that the liquid is added, and the Ph in the reactant is kept increasing in the direction of 5.5 to 8.5, and kept below 120 degrees for reaction for 8-16 hours, and the temperature is raised to 560 degrees at a temperature increase program of 3-6 degrees per minute, including adding to 5MPA when necessary, to form a substance BV of BaMn8O16, and BV is subjected to XRD analysis Fig.10 As shown below, diffraction peaks with 2θ of 25.637°, 28.728°, 12.73°, 37.49°, 41.9°, and 49.78° appear, which are consistent with those in BAMn8O16 in the card PDF#00-029-0188. By calculating that the factor is far from 1, it can be known that the substance is in an oxygen manganese octahedron, and the octahedron can deform and slide, increasing the electron transfer pathway and rate. The flexible and variable structure can make the substance have better catalytic properties. Furthermore, the flexible and variable structure cooperates with other substances to make the structure of the substance improve the adaptability and synergy of the material of the present invention and prevent the reduction of the effects of different molecular groups in the associated structure.
[0051] Furthermore, the first step includes adding 0.2-0.5 mole of potassium and aluminum to react to form a substance containing K2Al24O37. XRD results of the BV sample in the process include: Fig.11Based on the crystal diffraction, it is speculated that the formation of the substance is recorded as BV (k2Al 24O 37). The substance has a stable and strengthened bond. AL ions appear in the crystal, which has the effect of achieving better bonding with O, further improving the stability of the coordinated BV and its bonded substances. Furthermore, rare earths such as neodymium and other metals such as niobium and titanium can also be used in BV, which is beneficial to the appearance of mixed structural defects in BA materials.
[0052] In the second step, BV powder and X powder are mixed to form a powder of multifaceted active crystal catalyst material, and the NiO(OH)-containing material formed by X1 and BV is recorded as DZH1. DZH1 and n-hexane are prepared into a 30% solution and sprayed on carbon cloth to form a hydrogen production material or electrode to enhance the catalytic activity; similarly, samples BV, x1, x2, DZH1, and BVZ can be used alone, or prepared into a 30% solution with n-hexane and sprayed on carbon cloth to form a hydrogen production material. The relevant test hydrogen production results are shown in Fig.12a , 12b The relevant LSV curve in the figure can be further used to form an oxygen production and hydrogen production system by combining the A material and the B material of the present invention with the material for catalyzing hydrogen evolution of the present invention, including the BV, to promote catalytic hydrogen production. Preferably, the B material of the present invention and the hydrogen production material BV form a system or a hydrogen production system to achieve stable promotion of catalytic hydrogen production, and the sample is recorded as a BVB test;
[0053] Further, in order to improve the efficiency of hydrogen production, improve the adaptability of hydrogen production materials, or enhance the coordination and efficiency of different materials, the photocatalyst and BV are selectively reacted. Specifically, the O photocatalyst can be treated with ammonia to increase the reactivity of the diluted acidic substances. The substance BV is stirred and quickly sprayed on the diesel in a dotted manner, and some exchange channels of BV are retained to prevent reaction combination. Then, a solution with O configured into 0.5-1 is added. The solution is composed of water, ethanol and acetone in a ratio of 3:1:2, and the pH is adjusted to 5-7. The formed solution is dissolved in the crystalline BV at a constant temperature of 20- 60 degrees, stir the reaction to test the viscosity change, if the change does not increase by 1%, add hydrochloric acid to catalyze the reaction to ensure a slight increase in viscosity, stir the reaction for 45s to 10 minutes, filter it out, dry it at less than 102 degrees, and form BVZ powder. The test of BVZ shows that the molecular weight has increased by 53.3% compared with before the reaction. The cross-linking of barium and carboxyl groups by infrared detection has an absorption peak between 660-1160, which confirms the cross-linking with barium. The molecular structure of BVZ III is shown below. Through the detection of BV, it is found that a substance containing barium appears at the outer boundary of the material structure.
[0054]
[0055] The material has a BV part connected to the surface to generate a long-chain macromolecular electronic group with an O catalyst, and the BV is chemically modified by the complex O. The O-type catalyst is stably and firmly chemically combined with the BV containing the barium aluminum material through the above reaction modification, and the corresponding polycyclic pyridine structure is increased. The BVZ material with a flexible and changeable structure modified by O will realize the combination of inorganic and organic long-chain macromolecules, improve catalytic performance, increase the electron path, and collect and transfer electrons. Similarly, O1 is reacted with BV to form BVZO1, and BVZO1 is prepared with n-hexane into a 30% solution and sprayed on a carbon cloth to form a hydrogen production material. The BVZO1 hydrogen production material and the oxygen evolution C material of the present invention are composed of a system denoted as BVP, and the B material catalyzes oxygen evolution and BVZO 1. The material catalytic hydrogen evolution composition system is recorded as BBVZO1. The sample is tested for hydrogen evolution performance. Since the specific structural flexibility and combined stability of O-containing catalysts or BVZ-type substances cannot be specifically measured during hydrogen and oxygen production, a method for testing the structural flexibility of O-type catalysts or BVZ-type substances is provided. An O1 catalyst is selected to configure a 2% O1 solution, and a BVZ-type substance is configured with a 4% BVZ solution. The amount of O1 catalyst in the 2% BVZ solution is calculated to be 1% or an integer multiple of 1%, preferably 1% to facilitate the calculation of the corresponding amount performance of pure O1 catalysts or BVZ-type substances. The viscosity of the tested O1 solution and BVZ solution is between 180-220mpa.s. The structural performance or flexibility of the catalytic material is tested with an obstacle barrel. The obstacle barrel is as follows: Figure 13-14 As shown, Fig.13 a is a static image of the obstacle barrel. Fig.13 b The barrel sleeve is pulled up to a certain height. The barrier barrel includes an outer barrel 1 and an inner barrier barrel 2. A barrel sleeve 21 is arranged in the inner barrier barrel. A cutting ring 22 is threadedly connected to the bottom of the barrel sleeve. An obstacle channel 23 is arranged in the middle of the barrel sleeve. The channel 23 is preferably arranged in a pair of trapezoidal slopes. The opening slope of the upper trapezoid is greater than the opening slope of the lower trapezoid. The upper part of the cutting ring 22 is threadedly connected to the obstacle channel 23 at the lower end of the middle part of the barrel sleeve. Fig.14 , the cutting ring can be replaced by connecting with screws, an elastic column 3 is arranged on the outside of the inner obstacle barrel, and the inner obstacle barrel can seal and separate the elastic column 3 from the measuring liquid in the inner barrel 2, and the bottom plate of the elastic column 3 is fixed to the bottom of the outer barrel 1, and the upper handle 24 of the barrel sleeve 21 is movably connected to the upper part of the elastic column 3. By pulling the handle, the barrel sleeve 21 can be pulled to a certain height and the copper sleeve 21 can generate a downward pulling force through the elastic column 3. The pulling force can be measured by the tension gauge at the upper end of the elastic column. A gap plate 25 is arranged on the copper sleeve to adjust the steep rise of the liquid level or adjust the pressure. A balance shaft 26 is arranged on the upper part of the gap plate 25 to adjust the position and balance of the barrel sleeve. A scale 27 is arranged in the barrel sleeve, and the diameter of the bottom probe of the scale is preferably not less than the narrowest part of the obstacle channel. A fixing thread 11 is arranged at the bottom of the outer barrel to fix the obstacle barrel during testing. The method for using the obstacle barrel test of the present invention is as follows, Fig.13As shown in b, the barrel sleeve is pulled up to a certain height to release the tension, and the 316j1 cutting ring and the 316j1ru cutting ring are tested in parallel once, and the same tension is used for each test. The height L of the liquid passing through the two cutting rings or the obstacle channel and the mass value m of the liquid entering the obstacle channel are measured with the ruler in the copper sleeve. The height BVZL of the liquid passing through the two cutting rings or the obstacle channel is compared with the height O1L of the liquid passing through the two cutting rings or the obstacle channel of the O1 solution. The structural performance or its flexibility is compared with the 316j1 cutting ring containing the catalyst O1 material and the 316j1ru cutting ring. The external surface of the 1ru cutting ring in contact with the O1 material is XPS tested to analyze the affinity between the materials. Specifically, the barrier barrel is respectively filled with O1 solution and BVZ solution of the same scale, preferably the solution does not exceed the narrowest part of the barrier channel, the bottom thread connection of the barrel sleeve is equipped with a 316j1 stainless steel cutting ring, and the 316j1 stainless steel cutting ring is at least chemically plated with ruthenium on the surface to mark the 316j1ru cutting ring. The 316j1ru cutting ring can be tested with a ruthenium metal shell or outer cutting ring, or other general methods can be used to plate ruthenium. The surface of the 316j1 cutting ring is bright with the surface of the 316j 1ru cutting ring, preferably polished to level 4, the barrel sleeve is pulled to a certain height to produce the same tension release, and the 316j1 cutting ring and the 316j 1ru cutting ring is tested in parallel once, and the height L of the liquid passing through the two cutting rings or the obstacle channel and the mass value m of the liquid entering the obstacle channel are measured with the ruler in the copper sleeve, and the height value BVZL of the liquid passing through the two cutting rings or the obstacle channel is compared with the height value O1L of the liquid passing through the two cutting rings or the obstacle channel of the O1 solution. The structural performance or flexibility of the photocatalyst material is analyzed through the above comparison, and the external surface XPS test of the 316j1 cutting ring containing the catalyst O1 material and the 316j1ru cutting ring contacting the O1 material is performed to analyze the affinity between the materials. Specifically, the mass of the BVZ solution entering the 316j1 cutting ring is 5.6g and the height is 19mm, and the mass of the BVZ solution entering the 316j1ru cutting ring is 5.9g and the height is 21mm; the mass of the O1 solution entering the 316j 1 cutting ring is 4.3g and the height is 18mm, and the mass of the O1 solution entering the 316j1ru cutting ring is 4.8g and the height is 26mm.
[0056] The height BVZL of the BVZ solution passing through the obstacle cutting circle and the height L of the O1 solution passing through the obstacle corresponding cutting circle are used to compare the flexibility of the structure. Furthermore, the difference between the mass BVXm of the BVZ solution entering the cutting circle and the mass O1m of the O1 solution entering the corresponding cutting circle is used to compare the stability of the BVZ structure relative to the O1 catalyst. The more stable the structure is, the less likely it is to be damaged by cutting, and the pressure release deformation is poor. For example, in this test, the pressure release deformation is poor after passing through the obstacle cutting circle. The structure is flexible and has good sliding properties, and the better the compression deformation. For example, in this test, the BVZ solution is structurally stable and not easily damaged when subjected to external pressure cutting. The BVZ solution has a flexible structure and good deformation when subjected to pressure cutting. The mass entering the cutting circle is large, but the BVZ solution has a stable structure and releases the pressure shear force after entering the cutting circle, which is slightly slower than the O1 solution.
[0057] Furthermore, in order to measure the affinity between the catalyst O1 material and the cut ring, the cut ring 316j1 and the cut ring 316j1ru of the catalyst O1 material were subjected to an XPS test of the outer surface of the cut ring in contact with the O1 material. Fig.15 ,Depend on Fig.15 It can be seen that obvious characteristic peaks of P element are found on the outer surface of 316j1 cutting ring. The phosphorus element is speculated to come from the phosphorus element in O1 material, while the 316j 1ru cutting ring is relatively weak. The amount of phosphorus in metal ruthenium is low or undetectable, and the visibility is poor. It may be caused by the slight loss of ruthenium coating, which leads to X-ray irradiation to the surface of 316j1. At the same time, the XPS test of the outer surface of the same 316j1 without contacting O1 material is tested separately, such as Fig.15 The phosphorus content in the curve of the 316j1 stainless steel is not high either. Fig.15 It can be seen that there is p element on the surface of 316j1, but the intensity content is much lower than that of the surface of 316j1 in contact with O1 material. It can be inferred that O1 material has affinity and adsorption with copper, iron, nickel, chromium, manganese, etc., and has no obvious adsorption and combination with metal ruthenium. The same liquid in the above test is tested with 316j1 cutting circle and 316j1ru cutting circle. The results of slight differences in the mass and height of the liquid entering also reflect this conclusion, indicating that metal ruthenium has the ability to weaken the adsorption and combination of O1 material. For the present invention, the contact or mixed use of materials catalyzing oxidative oxygen evolution with O1 material is minimized to reduce the reverse transfer of electron current, thereby weakening the reduction hydrogen evolution performance or weakening the combination of O1 material and catalytic hydrogen evolution material or oxidizing and destroying O1 material. It is speculated that ruthenium metal has the function of preventing reverse catalysis. The internal hydroxyl material containing MoO·HO or the material containing Cu 7x (Mo+6 )2 (Mo+2)O 12 (OH) 4,A metal ruthenium material is disposed on the surface of the internal hydroxyl material to ensure the activity of the O-type catalyst or to form an anti-reversal system. Unless otherwise specified in this article, the testing of the O-type catalyst is carried out under the conditions of required light.
[0058] This method can quickly and relatively measure stability and flexibility. The measurement results are not mutually exclusive with the results of the LSV curves of O catalysts and BVZ substances. The structure of the LSV curve illustrates the reliability of the relative measurement results from another perspective. It can also test the catalytic performance of a single O catalyst and verify its initial electrical parameters involved in catalysis. Specifically, a workstation is selected, a carbon rod is used as a counter electrode, and a mercury / mercury oxide electrode is used as a reference electrode. Under the required light conditions, 0.1 molar sulfuric acid is used as a test solution, and a voltage of 1v is used to test the initial current of 8mA. Under the same conditions, 0.1 molar O catalyst is added as an initial current of 11mA.
[0059] Furthermore, BVZ substance is mixed with X powder to form a powder of multi-faceted active crystal catalytic material, BVZ and x1 form a material containing Nio(OH) denoted as DZH2, DZH2 and n-hexane are prepared into a 30% solution and sprayed on carbon cloth to form a catalyst denoted as hydrogen production material to enhance catalytic activity, and the test results are shown in the relevant LSV curve in Figure 12; preferably, in order to better prevent BV material from being damaged by O-type photons in a high-temperature electrolysis environment or causing the combination of the two to be unstable, BVZ can be adsorbed on an insulating material silicon dioxide with a slightly larger particle size than BV, and then prepared with n-hexane into a 30% solution and sprayed on carbon cloth to form a catalyst denoted as BVZSI, and the catalytic activity of the BVZSI hydrogen production material is tested. Figure 12b The BVZSI curve in the figure shows that the BVZSI curve of silicon has less voltage at the same current. If the test does not achieve the effect of less voltage at the same current, according to the test Figure 12b The LSV curve results shown in the figure are adjusted by adjusting the material matching of the invention so that the voltage of the invention material is lower under the same current.
[0060] The LSV curve of the prepared catalyst sample is measured using an electrochemical workstation. The test is preferably carried out in an alkaline solution, such as a solution with a pH of 9. The test conditions of the same type of line are kept consistent. The test results are as follows: Fig.12a , 12bAs shown, in FIG12 a, the oxygen evolution performance of the oxidation reaction material is shown. It can be seen from the figure that the A material has good oxygen evolution performance, and an inflection point appears at 1.6V. In FIG12 b, the hydrogen evolution performance of the material is shown. It can be seen from the figure that the material BV shows the performance of hydrogen evolution. The hydrogen evolution performance of the BVB system composed of the B material and / or BV is better than that of each material alone. Further, according to the position of the curve b in the figure, it can be seen that the BVB on the right side of the curve is also better. Therefore, the effect of using the two materials as a system exceeds the effect of simple superposition when used alone, which further illustrates that the B material and / or BV constitute After the combination of the two materials, there was no weakening of the effect or weakening of the current, resulting in attenuation or reverse reaction of the materials including NiO(OH), while the system composed of C material and O1 was recorded as BVP, which underwent hydrogen evolution attenuation. It is speculated that the copper, nickel, cerium or molybdenum in the C material may have contacted or mixed with the O1 material, resulting in reverse electron transfer or reverse current or material decomposition and damage, resulting in reduced hydrogen evolution performance of the system. After the B material with a ruthenium metal outer layer was combined with the O1 material into a system, the above-mentioned reverse current did not occur, which is basically consistent with the inference in the material structure flexibility test method that ruthenium metal has an anti-reverse catalytic effect, which is beneficial to the formation of an anti-reverse system.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for testing the catalytic hydrogen production performance of an O-containing catalyst, characterized in that: Select a workstation, use a carbon rod as an electrode, and a mercury / mercury oxide electrode as a reference electrode. Under light conditions, use sulfuric acid as a test solution and use voltage to test the initial current. Under the same conditions, add a certain mole of O-type catalyst as the initial current; the O-type catalyst contains at least the following molecular structure I catalyst.
2. A method for testing the structure of a hydrogen production catalyst, characterized in that: First, prepare the O1 catalyst solution and the BVZ material solution, test the viscosity of the O1 solution and the BVZ solution, and use an obstacle barrel to test the performance of the solution. The obstacle barrel includes a barrel sleeve, a ring cutter, and an obstacle channel. The barrier barrel is respectively filled with the O1 solution and the BVZ solution of the same scale. The barrier barrel is equipped with a 316j1 ring cutter and a 316j1ru ring cutter. The barrel sleeve is pulled up to a certain height to release the tension. The 316j1 ring cutter and the 316j1ru ring cutter are used in parallel for testing once, and the barrel sleeve is used to test the performance of the solution. A ruler is used to measure the height L of the liquid passing through the two cutting knives or the obstacle channel and the mass value m of the liquid entering the obstacle channel. The height BVZL of the liquid passing through the two cutting knives or the obstacle channel is compared with the height O1L of the liquid passing through the two cutting knives or the obstacle channel of the O1 solution to measure the material structure performance or its flexibility. XPS test is performed on the external surface of the 316j1 cutting knife that cuts the catalyst O1 material and the 316j1ru cutting knife that contacts the O1 material to analyze the affinity between the materials.
3. The testing method according to claim 2, characterized in that: In the test, the BVZ solution has a stable structure and is not easily damaged when subjected to external pressure and cutting. The BVZ solution has a flexible structure and is well deformed when subjected to pressure and cutting, which reflects the quality of the test process or result of entering the circle cutting knife. The BVZ solution has a stable structure and releases the pressure and cutting force after entering the circle cutting knife, and its deformation speed is slightly slower than that of the O1 solution.
4. The testing method according to claim 3, characterized in that: In order to check the affinity between the catalyst O1 material and the cutting knife, XPS was performed on the outer surfaces of the cutting knives 316j1 and 316j1ru where the cutting knives were in contact with the O1 material to measure the characteristic peaks of the P element on the outer surface of the 316j1 cutting knife.
5. The testing method according to claim 4, characterized in that: The barrier barrel comprises an outer barrel and an inner barrier barrel. A barrel sleeve is arranged in the inner barrier barrel. A ring cutting knife is threadedly connected to the bottom of the barrel sleeve. An obstacle channel is arranged in the middle of the barrel sleeve. The channel is arranged in a pair of trapezoidal slopes. The opening slope of the upper trapezoid is greater than the opening slope of the lower trapezoid. The upper part of the ring cutting knife is threadedly connected to the barrier channel at the lower end of the middle part of the barrel sleeve. The ring cutting knife can be replaced by screw connection. An elastic column is arranged on the outside of the inner barrier barrel. The inner barrier barrel can seal and separate the elastic column from the measuring liquid in the inner barrel. The bottom plate of the elastic column is fixed to the bottom of the outer barrel. The upper handle of the barrel sleeve is movably connected to the upper part of the elastic column. The barrel sleeve can be pulled up to a certain height by pulling the handle.
